2005
DOI: 10.1007/s00228-005-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of long-term medication use after surgical hospital stay

Abstract: The observed changes in medication after hospitalization can be only partially attributed to a successful surgical intervention and to the hospital stay. Those alterations seemed not to be initiated by the intention of saving costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
6
0
5
Order By: Relevance
“…This may indicate that some of the attending physicians focused on symptomatic treatment of the medical condition. Patients with ACS took an average of six medications and patients with stroke took an average of five medications, which is in the upper range reported in the literature (Hach et al 2005;Harder et al 2005). It was also found that polypharmacy can be caused by treatment according to evidence-based therapeutic guidelines, which is particularly problematic for elderly and multi-morbid patients (Meinertz and Kähler 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may indicate that some of the attending physicians focused on symptomatic treatment of the medical condition. Patients with ACS took an average of six medications and patients with stroke took an average of five medications, which is in the upper range reported in the literature (Hach et al 2005;Harder et al 2005). It was also found that polypharmacy can be caused by treatment according to evidence-based therapeutic guidelines, which is particularly problematic for elderly and multi-morbid patients (Meinertz and Kähler 2005).…”
Section: Discussionmentioning
confidence: 95%
“…As a result, modifications in pharmaceutical treatment were found to various degrees and at different stages in the course of continued medical care (Hach et al 2005;Himmel et al 2004;Taxis and Schneeweiss 2003). Inconsistency in prescription behaviour is especially problematic when dealing with medications with a proven benefit for preventing serious adverse health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of interorganizational collaboration was found to be associated with discontinuity of care, for instance, regarding pharmacotherapy (Adl et al, 2001;Hach, Maywald, Meusel, König, & Kirch, 2005). In studies conducted with hospitalized patients, perceived coordination and continuity of care were found to be a determinant of the overall evaluation of care (Berendsen, de Jong, Meyboom-de Jong, Dekker, & Schuling, 2009;Jenkinson et al, 2002).…”
Section: Previous Researchmentioning
confidence: 94%
“…In order to test this, the authors concentrated on the medication administered on admission to hospital and provided considerable evidence of changes in the prescriptions during the stay in hospital. Hach et al [16] show that hospitalization neither saves the ambulatory follow-up treatment nor is accompanied by a reduction in medication.…”
Section: Introductionmentioning
confidence: 99%